تقييم تطبيق مناهج التعليم العام في مدارس الأطفال المعاقين بصريا. - منير بشاطة (Université de M'sila, 2021)
The study aims to assess the application of the canvas and general education programs in schools specializing in the education of blind children with disabilities in algies and m’sila and biskra according to the technical staff involved in the care charge of this category and following the investigation of the reality of teaching in specialized schools . To do this, the researcher adopted the descriptive analytical method and conducted a quantitative study with 80 members of the technical staff from various professions and disciplines involved in the process of care within a few specialized schools . The results of the study revealed that the frameworks intended and applied in general education in schools specializing in the education of blind children are able to
Keywords: general education curricula; visually handicapped; éducatif teams specialized